Flow-mediated modulation of the endothelial cell lipidome - Hong, Soon-Gook; Kennelly, John P.; Williams, Kevin J.; Bensinger, Steven J.; Mack, Julia J. (Frontiers in Physiology, 2024)
The luminal surface of the endothelium is exposed to dynamic blood flow patterns that are known to affect endothelial cell phenotype. While many studies have documented the phenotypic changes by gene or protein expression, less is known about the role of blood flow pattern on the endothelial cell (EC) lipidome. In this study, shotgun lipidomics was conducted on human aortic ECs (HAECs) exposed to unidirectional laminar flow (UF), disturbed flow (DF), or static conditions for 48 h. A total of 520 individual lipid species from 17 lipid subclasses were detected. Total lipid abundance was significantly increased for HAECs exposed to DF compared to UF conditions. Despite the increase in the total lipid abundance, HAECs maintained equivalent composition of each lipid subclass (% of total lipid) under DF and UF. However, by lipid composition (% of total subclass), 28 lipid species were significantly altered between DF and UF. Complimentary RNA sequencing of HAECs exposed to UF or DF revealed changes in transcripts involved in lipid metabolism. Shotgun lipidomics was also performed on HAECs exposed to pro-inflammatory agonists lipopolysaccharide (LPS) or Pam3CSK4 (Pam3) for 48 h. Exposure to LPS or Pam3 reshaped the EC lipidome in both unique and overlapping ways. In conclusion, exposure to flow alters the EC lipidome and ECs undergo stimulus-specific lipid reprogramming in response to pro-inflammatory agonist exposure. Ultimately, this work provides a resource to profile the transcriptional and lipidomic changes that occur in response to applied flow that can be accessed by the vascular biology community to further dissect and extend our understanding of endothelial lipid biology.